IMPLEMENTASI PROGRAM IRAMA NEGERI DALAM MENINGKATKAN KARKATER PATRIOTISME PADA SISWA SEKOLAH DASAR - Naura Diki Anggi Fhalentina; M. Bambang Edi Siswanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of singing national and regional songs through the Irama Negeri program as a strategy to enhance the patriotism of elementary school students. The background of this study is based on the phenomenon of declining interest and appreciation of students towards national songs and limited appreciation of regional songs, especially amid the trend of digital popular culture. The research uses a qualitative approach with techniques of interviews, observation, and documentation involving upper grade teachers, lower grade teachers, and student representatives from each class. The results show that the habit of singing national and regional songs can be an effective means of instilling the value of love for the country if done consistently and supported by creative learning methods. Teachers play an important role in integrating the meaning of songs through storytelling, visualization, and collaborative activities so that students are able to understand the value of patriotism in concrete terms. Structural support from schools in the form of regular schedules, song guides, and the provision of learning media are important factors in the success of the program. Thus, singing activities can be a strategic instrument in strengthening students' national character from an early age.